EFFORTS TO IMPROVE READING ABILITY THROUGH LETTER CARD GAMES IN CHILDREN AGED 5-6 YEARS - Jamilah, Ayu Fajarwati, Afifah (Jurnal Pendidikan dan Penelitian Serumpun Mendidik, 2025)
Jasturi, 2024 was motivated by the problem of reading ability in Kober Anugrah, Binuang District, Serang Regency which was still not optimal. So the researcher wanted to improve reading ability by creating a thesis title "Efforts to Improve Reading Ability Through Letter Card Games in Children Aged 5-6 Years in Sukamampir Village, Binuang District, Serang Regency" The purpose of this study was to see an increase in reading ability through letter card games and to improve reading ability through letter card games in children aged 5-6 years in Kober Anugrah. The research time was Tuesday, July 30, 2024 in Kober Anugrah, Binuang District, Serang Regency. The research subjects in Kober Anugrah were 8 children out of 5 girls and 3 boys, the objects of the research assisted by 4 teachers. The instruments used were assessment of observation data analysis, interviews and questionnaires. The method used was Classroom Action Research which was carried out in two cycles and consisted of 10 meetings, each cycle consisting of 4 activities, namely planning, implementation, observation and reflection. The results of this study showed that the average reading ability in cycle 1 was 31 children who had not developed or 77.5%, 6 children who had started to develop or 15%, 3 children who were developing according to expectations or 7.5%, while in cycle 2 the number of children who had not developed or 3 could be 7.5%, 15 children who had started to develop or 37.5%, 20 children who were developing according to expectations or 50%, 2 children who were developing very well or 5%. So it can be concluded that with the implementation of the letter card game, children are invited to play arranging the alphabet A-Z letter cards, children are invited to mention the letters A-Z, children are invited to group vowels and consonants, and to compose syllables and words. So that the reading ability of children aged 5 to 6 years in Kober Anugrah, Sukamampir Village, Binuang District, Serang Regency can increase according to expectations and develop very well.